Forming Market Instruments of Import Substitution Strat- egy in Russia As A Result of The Sanctions Policy Related to Events in Ukraine - Mikhailovna Chernysheva, Anna; Andreevna Degtereva, Ekaterina; Alexandrovna Trofimova, Alexandra (Opción, 2019)
The import substitution forms a policy to protect the national producer by prohib- iting the import of products and substituting them with the domestic ones. As a result, the competitiveness of domestic products grows and moves from everyday goods to high-tech production. On October 1, 2014, the Government of the Russian Federation adopted the import substitution strategy “Development of Industry and Enhancing its Competitiveness”, above all, in industry. The import substitution strategy is introduced in various sectors of the national economy, including the fuel and energy complex, consumer, forestry and automotive industry, pharmaceuticals, etc. (Beksultanova, 2016). The formation of the import substitution strategy was caused, firstly, by the depreciation of the ruble in 2013-2014, and, secondly, by the decrease in import due to the sanctions policy against Russia related to the situa- tion in Ukraine. At the same time, today the Russian economy is highly dependent on intermediate and final goods for investment purposes. In the sectoral programs of import substitution, it is planned to considerably reduce such dependence by 2020 (Pavlov, Kaukin, 2017). In this case, the decrease in the dependence on world producers should not become an isolated and closed system. That is why the inte- gration of the domestic producer into the global value chains will be an additional goal. This means that it will also increase competitiveness in the global market. Nevertheless, it is necessary to understand that in the context of investment goods, the Russian economy is highly dependent on global prices for raw energy products, which necessitates the production of final investment goods on the territory of Rus- sia. The publication has been prepared with the support of the “RUDN University Program 5-100” within the project “Improvement of marketing tools to support and expand the import of consumer goods in the real sector of the Russian economy”.